Case study obstetrics care pregnant women a multipara mammal with anemia lightly on TrimesterII In PMB - feby (Sekolah Tinggi Ilmu Kesehatan Gunung Sari, 2023)
Anemia for pregnant women are closely connected to mortalitas and morbidity and babies, on the including miscarriage, risk stillborn, the prematurity of low birth and birth weight. Maternal mortality indonesia in general caused by several factors. First, obstetrics directly cause bleeding, covering preeklampsi / eklampsi, infection and cause not directly the problems the nutrition covering anemia for pregnant women, lack of energy chronic and pregnant women with energy consumption under needs at least . The purpose of this research to know intervensi case study obstetrics care pregnant women a multiparous mammal with anemia light pmb love mother.In case study method used the case study obstetrics care given for pregnant women a multiparous mammal mrs 35 years of age giv pii pun ai, 29 week of gestation, complaints dizzy, nausea vomiting, too come on tired and while doing activity use sabun. An analyzer used comparing between existing data he with the theory .Case study the care of obstetrics has been conducted .Study until penatalaksanaan and no gaps the theory and the fact he and complaint mother over dizzy , the origination and weary in consume. can be handled.